Cosmografías musicales en culturas prehispánicas del suroccidente Colombiano - Pinilla Higuera, Germán (Cali : Programa Editorial Universidad del Valle, 2009)
Musicological research in the archaeological context are very rare and have not been sufficiently disseminated in academic circles. This study inventories and describes items collected, studied and categorized in different museums in Colombia and those are significant collections of various musical instruments in various archaeological materials and technologies. There is an emphasis on the iconographic/artistic elements of the instruments.
Lo sonoro y su materialización cultural -- Los llama : cultura material e instrumentos sonoro-rituales -- Culturas Piartal y Tuza : naturaleza, cosmogonías y cosmografías musicales -- Culturas Mulato : lenguajes rituales con tierra, agua y fuego.
Incluye referencias bibliográficas. (páginas [77]-79).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Ocarina -- Colombia -- History; Indians of South America -- Colombia -- Music -- History and criticism; Folklore de Colombia; Música de Colombia; Instrumentos musicales de Colombia; Arqueología de Colombia; Prehistoria de Colombia; Colombia -- Antiquities; Colombia prehispánica.; Valle del Cauca; Libros electrónicos.